Mass animal sacrifice at casas del Turuñuelo (Guareña, Spain): A unique Tartessian (Iron Age) site in the southwest of the Iberian Peninsula - Iborra Eres, Mª Pilar; Albizuri, Silvia; Gutiérrez Rodríguez, Mario; Jiménez Fragoso, Joaquín; Lira Garrido, Jaime; Martín Cuervo, María; Martínez Sánchez, Rafael M.; Martínez Valle, Rafael; Mayoral Calzada, Ana Isabel; Nieto Espinet, Ariadna; Rodríguez González, Esther; Valenzuela-Lamas, Silvia; et al. (PLOS ONE, 2023)
Zooarchaeological analyses of the skeletal remains of 52 animals unearthed in the courtyard of an Iron Age Tartessian building known as Casas del Turuñuelo (Badajoz, Spain) shed light on a massive sacrifice forming part of a series of rituals linked to the site’s last period of activity and final abandonment. The rites took place towards the end of the 5th century BCE when both the building (intentionally destroyed) and the sacrificed animals were intentionally buried under a tumulus 90 m in diameter and 6 m high. The main objective of the zooarchaeological and microstratigraphic analyses was to determine the phasing of the sacrificial depositions. Evidence gathered from taphonomic assessments and a series of radiocarbon datings indicate that the sacrifices fall into three consecutive phases spanning several years. The findings of the zooarchaeological analyses clearly point to a selection of equid and cattle males. Adult equids predominate (MNI = 41) followed by adult and sub-adult cattle (MNI = 6). Pigs, in turn, are only represented by a few adults and sub-adult females (MNI = 4). Among the animals is a single dog of undetermined sex between 3 and 4 years of age. The fact that the animals are mostly adults discards the likelihood that they died from natural causes or an epidemic. In addition, the scenographic deposition of certain equids in pairs, as well as evidence of the burning of plant offerings, suggest an intentional ritualistic sacrifice. Nine of the initial depositions of Phase 1 in the SE quadrant were scattered and certain of their bones bear marks characteristic of both prolonged open air exposure and scavengers. Another 31 animals from Phases 1 and 2 are represented by almost complete, articulated skeletons, indicating they were promptly covered. Phase 3, by contrast, reveals both almost complete and partial animals bearing clear signs of processing for human consumption. This study thus sheds light on both the sequence of the animal sacrifices and the protocols linked to rites accompanied by the celebration of banquets. Certain features associated with the sealing of this building under a tumulus offer evidence of the decline of the Tartessian Culture. This study thus advances notions serving to contextualize ritual animal sacrifices in the framework of practice observed at other Iron Age sites in the Iberian Peninsula and elsewhere throughout Europe.